2017
DOI: 10.1111/gec3.12352
|View full text |Cite
|
Sign up to set email alerts
|

Electoral geography: From mapping votes to representing power

Abstract: In some ways, electoral geography has never been more popular. From the detailed, online maps of the Brexit vote to discussions of the electoral college versus the popular vote in the 2016 Trump–Clinton U.S. presidential contest, the relationships among geography, voting, and political power have seldom been more visible. The popularity of electoral geography in social and news media, however, does not necessarily reflect its presence in scholarly discussions, and indeed, in some ways, the former has replaced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 104 publications
(143 reference statements)
0
14
0
3
Order By: Relevance
“…Although Ghitza and Gelman (2013) showed that by means of multilevel models and post-stratification (MPR) we can quite precisely model and map the different behaviour of voters group across 50 American states, this method is not viable in countries with a smaller number of secondlevel units, such as the Czech Republic. Generally, the practice of using polling data is relatively limited among electoral geographers (Forest, 2018).…”
Section: Analysing Electoral Results In Political Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Although Ghitza and Gelman (2013) showed that by means of multilevel models and post-stratification (MPR) we can quite precisely model and map the different behaviour of voters group across 50 American states, this method is not viable in countries with a smaller number of secondlevel units, such as the Czech Republic. Generally, the practice of using polling data is relatively limited among electoral geographers (Forest, 2018).…”
Section: Analysing Electoral Results In Political Sciencementioning
confidence: 99%
“…The lower the level of the aggregation of data provided by the Statistical Office the better (e.g. precinct data would be superior to municipal level data), but the ultimate disadvantage of this is that we are unable to understand voter behaviour at the individual level, commonly known as the ecological fallacy (see Forest, 2018). We are completely unable to inspect hypotheses that are attitudinal or emotional (Kouba & Lysek, 2019).…”
Section: Analysing Electoral Results In Political Sciencementioning
confidence: 99%
“…Forward Sortation Areas (FSA), derived from Canadian postal codes, are used as a proxy for neighborhoods, and Statistics Canada provides census data for these units. Model 2 has been included because, within political geography, scholars have argued that contextual effects have an impact on voter behaviour and opinions (Forest, 2018; Walks, 2006). Model 3 adds opinion‐based variables: self‐reported ideology on a left–right ideological scale, level of dissatisfaction with democracy, belief that the economy has become worse in the last year, and feelings toward racial minorities in general, immigrants, and feminists.…”
Section: Methodsmentioning
confidence: 99%
“…where k = 1,2, … ,q = number of districts A k = PartyAswasted votes in districtk B k = Party Bs wasted votes in k T = Total votes cast in all district races. The increasing sophistication of partisan districting plans and rising political polarization have been among the reasons for significantly revived academic attention now being paid to electoral geography (Warf and Leib 2011;Forest 2017). The efficiency gap approach is distinctly different from most academic literature on spatial fairness in electoral districting.…”
Section: Introductionmentioning
confidence: 99%